EXPLORING CHINA’S BELT AND ROAD INITIATIVE IN SOUTHEAST ASIA’S SUSTAINABILITY AGENDA: FROM GROWTH TO EQUITY? - Asy’ari, Munjin Syafik; Fadillah, Andi Axl Azslam; Baharuddin, Aswin; Oktaviano, Nandito; Cangara, Abdul Razaq (UI Scholars Hub, 2026)
This article evaluates the Belt and Road Initiative (BRI) through the analytical framework of sustainable development. The framework is crucial, as China frequently disseminates sustainability claims to promote the BRI. To assess these claims, it is necessary to examine the realisation of BRI projects alongside the empirical consequences they have generated across recipient countries. Southeast Asia constitutes one of the most prominent target regions for BRI investment. Four Southeast Asian countries occupy a significant position due to the scale and number of projects they have received: Indonesia, Malaysia, Vietnam, and Thailand. Each country exhibits distinct political–economic systems and structural conditions, rendering them analytically salient cases for testing the BRI as a purportedly sustainable development cooperation project. The findings indicate that BRI projects contribute to economic growth, primarily through enhanced connectivity, yet they fall short of fulfilling the core elements of sustainable development. Case studies from the Philippines, Malaysia, Vietnam, and Indonesia reveal environmental impacts, including deforestation, biodiversity loss, and social displacement resulting from land-use conversion. The policy orientation of the BRI has not fully embodied a holistic commitment to sustainable development principles, as it remains more oriented toward economic gains than toward ecological balance and social justice. To align the BRI more closely with the 2030 Agenda, China would need to enforce stricter environmental standards, enhance transparency in financing mechanisms, and prioritise investment in renewable energy.